Annexin A1 N-Terminal Derived Peptide Ac2-26 Exerts Chemokinetic Effects on Human Neutrophils - Dalli, Jesmond; Montero-Melendez, Trini; Perretti, Mauro (Frontiers in Pharmacology, 2012)
It is postulated that peptides derived from the N-terminal region of Annexin A1, a glucocorticoid-regulated 37-kDa protein, could act as biomimetics of the parent protein. However, recent evidence, amongst which the ability to interact with distinct receptors other then that described for Annexin A1, suggest that these peptides might fulfil other functions at variance to those reported for the parent protein. Here we tested the ability of peptide Ac2-26 to induce chemotaxis of human neutrophils, showing that this peptide can elicit responses comparable to those produced by the canonical activator formyl-Met-Leu-Phe (or FMLP). However, whilst disruption of the chemical gradient abolished the FMLP response, addition of peptide Ac2-26 in the top well of the chemotaxis chamber did not affect (10 µM) or augmented (at 30 µM) the neutrophil locomotion to the bottom well, as elicited by 10 µM peptide Ac2-26. Intriguingly, the sole addition of peptide Ac2-26 in the top wells produced a marked migration of neutrophils. A similar behaviour was observed when human primary monocytes were used. Thus, peptide Ac2-26 is a genuine chemokinetic agent towards human blood leukocytes. Neutralization strategies indicated that engagement of either the GPCR termed FPR1 or its cognate receptor FPR2/ALX was sufficient to sustain peptide Ac2-26 induced neutrophil migration. Similarly, application of pharmacological inhibitors showed that cell locomotion to peptide Ac2-26 was mediated primarily by the ERK, but not the JNK and p38 pathways. In conclusion, we report here novel in vitro properties for peptide Ac2-26, promoting neutrophil and monocyte chemokinesis, a process that may contribute to accelerate the resolution phase of inflammation. Here we postulate that the generation Annexin A1 N-terminal peptides at the site of inflammation may expedite the egress of migrated leukocytes thus promoting the return to homeostasis.